(untitled) (Herald of Journalism, 2020)
In this article a political culture and her influence are examined on be- havior of people and on activity of different organizations, on their percep- tion of the phenomena of domestic and international policy, estimation of the political leaders, and determination by the man’s place in the political life of the society.